EFFECTIVENESS OF LAWSONIA INERMIS LINNEAUS LEAVES INFUSION IN GINGIVITIS HEALING: EFEKTIFITAS INFUSA DAUN LAWSONIA INERMIS LINNEAUS TERHADAP PENYEMBUHAN GINGIVITIS - Lies Zubardiah; Dewi Nurul Mustaqimah; Elza Ibrahim Auerkari (Dentika: Dental Journal, 2012)
Gingivitis is one type of periodontal disease and it is chronic in nature. The main etiological factor of gingivitis is bacterial plaque. Untreated gingivitis can spread to underlying tissues and it can become periodontitis and produce tissue destruction. One of the treatments for gingivitis is plaque removal, helped by antibacterial mouthrinsing to reduce bacterial plaque. Lawsonia inermis L. leaves have been used by Indonesian villagers for healing skin wounds and reported to show antibacterial effect in vitro and in vivo. This study aimed to determine the effect of Lawsonia inermis L. leaves infusion in gingivitis healing. A total of 63 gingivitis patients devided into 5 groups were instructed to rinse with 3 concentrations (50000 µg/mL, 10000 µg/mL, 5000 µg/mL) of Lawsonia inermis L. leaves infusion; 0.1% hexetidine solution, and placebo as control. Papilla Bleeding Index (PBI) used in measurement for bleeding on probing. The result showed that decreasing of PBI in Lawsonia inermis L. leaves infusion at 10000 µg/mL concentratation (80%), was stronger than hexetidine 0.1% (76%). In conclusion, Lawsonia inermis L. leaves infusion effective to reduce PBI better than hexetidine. In conclusion, Lawsonia inermis L. leaves is effective to treat gingivitis.